Penggunaan Aplikasi Mobile Learning pada Mata Pelajaran IPS untuk Meningkatkan Prestasi Belajar Siswa di SMP Negeri 2 Rongga Kabupaten Bandung Barat - Deden Sodikin; Neneng Tripuspita; Khaerul Syobar (Departement of Mathematics Education, 2024)
This research is motivated by the emergence of the problem of low student learning motivation because learning resources are often limited to textbooks and materials provided by teachers, which can hinder students' access to wider information resulting in a lack of desire to learn. The aim of this research is to find out and examine the relationship between the application of mobile learning and increasing student learning achievement in social studies subjects at SMP Negeri 2 Rongga, West Bandung Regency. Data collection techniques use interviews, observation and documentation. The method used in this research is a quantitative descriptive method. The research sample consisted of 32 class IX students for the 2023/2024 academic year. The research results showed that there was a positive and significant influence of the intensity of using mobile learning as a learning medium on student learning achievement at SMP Negeri 2 Rongga, West Bandung Regency. The results of hypothesis testing using Simple Linear Regression analysis show the significance of the regression coefficient (t test) of (p-value = 0.002 < 0.05). and the resulting regression model is: Learning Achievement (Y)=3.734+0.002×Intensity of Mobile Learning Use (X)